A Biological Theory of Social Discounting - Robson, Arthur J.; Szentes, Balázs (American Economic Review, 2014)
We consider a growth model in which intergenerational transfers are made via stocks of private and public capital. Private capital is the outcome of individuals' private savings while decisions regarding public capital are made collectively. We hypothesize that private saving choices evolve through individual selection while public saving decisions are the result of group selection. The main result of the paper is that the equilibrium rate of return to private capital is at least 2–3 percent more than the rate of return to public capital. In other words, social choices involving intertemporal trade-offs exhibit much more patience than individual choices do. (JEL D11, D71, D91, H43)